EVALUATION OF FEED GRADE ENZYMES BY INVITRO METHOD USING DE OILED RICE BRAN (DORB) AS SUBSTRATE - R. Kavitha; D. Chandrasekaren (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Commercial cocktail enzymes were collected from the market and evaluated for enzyme activity. Among the enzyme preparations which is having more enzyme activity was selected for invitro evaluation by using de oiled rice bran as substrate. The results of the present study indicated that a significant (P < 0.05) and linear increase in the release of glucose and reducing sugars with the increase in the level of enzyme mixtures from 0 to 7.5 mg / 10 g of DORB.